A Design Approach to Forge Visions That Amplify Paths of Peri-Urban Development. (April 2013) - Rauws, Ward; van Dijk, Terry
Peri-urban areas are generally highly dynamic and fragmented zones. This is due not only to their functional and physical diversity and fragmentation, but also because they are the focus of a wide variety of perceptions and interests. This plurality causes on-going planning difficulties, affecting planners' ability to identify and strategically strengthen common interests for future development. In this paper we claim that spatial visioning can be supportive in bridging the gap between contested 'perceived peri-urban realities' by revealing shared values and devising innovative ideas that blend seemingly contradictory demands. However, we suggest that visioning processes need designers to spark imagination effectively and make visioning more productive. Designers can bring together unexpected combinations of stakeholders by redefining problems, strengthen the link between process and content, and take responsibility for integral and appealing vision products.